2011
DOI: 10.1177/0363546511416317
|View full text |Cite
|
Sign up to set email alerts
|

Is the Anterior Tibial Artery Safe During Ankle Arthroscopy?

Abstract: In 22 (6.2%) of the 358 cases, the ATA and its branches were located near the anterolateral ankle portal, which introduces the risk of vascular damage during arthroscopic surgery. Furthermore, the mean distance between the ATA and the joint capsule was only 2.3 ± 1.1 mm, and thus the ATA is very close to the anterior working space of the ankle joint. Careful preoperative evaluation and an intra-articular procedure may reduce the risk of vascular complications attributable to ankle arthroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 19 publications
0
14
0
2
Order By: Relevance
“…However, little information is available regarding vascular damage during ankle arthroscopy, especially anatomical variations of the anterior tibial artery (ATA). According to a previous study [5], the ATA might be at risk from anterolateral portals during ankle arthroscopy. The present study found that the ATA and the perforating branch of the peroneal artery crossed the reference line at 49.6% and 22.0% of the reference line from the most prominent point of lateral malleolus, respectively (Table 4); the intersection points according to the x- and y -coordinates are shown in Table 5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, little information is available regarding vascular damage during ankle arthroscopy, especially anatomical variations of the anterior tibial artery (ATA). According to a previous study [5], the ATA might be at risk from anterolateral portals during ankle arthroscopy. The present study found that the ATA and the perforating branch of the peroneal artery crossed the reference line at 49.6% and 22.0% of the reference line from the most prominent point of lateral malleolus, respectively (Table 4); the intersection points according to the x- and y -coordinates are shown in Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…Son et al [5] also reported an anterior tibial artery injury rate of 4.3% during anterior ankle arthroscopy. Specifically, damage of the superficial peroneal nerve has been a focus of some authors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While similar cases of AT pseudoaneurysms exist in the literature, this particular case is notable for the location in the DP artery, the size of the pseudoaneurysm, late presentation, and eventual rupture. 28 …”
Section: Discussionmentioning
confidence: 99%
“…3,14 However, deviation of AT toward the anterolateral port site is present in 6.3% of patients, making pre-operative confirmation of vascular anatomy a crucial part of ankle arthroscopy. 8 Furthermore, in 2–12% of patients, the DP arises aberrantly from the peroneal artery. 15,16 In the case described above, existing scarring and the need to extend the typical arthroscopic portal site into an arthrotomy increased the risk that the artery wall would be damaged during removal of the osteophytes.…”
Section: Discussionmentioning
confidence: 99%